Academic adjustment and socio-economic legacy effects: Evidence from the years of the #FeesMustFall and #RhodesMustFall protests - Papageorgiou, E.; Callaghan, C.W. (South African Journal of Higher Education, 2020)
<span style="font-family: ’New TIMES ROMAN’,’serif’; font-size: 12pt; mso-fareast-font-family: Calibri; mso-bidi-font-family: Arial; mso-ansi-language: EN-ZA; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-ZA">South Africa’s higher education sector experienced widespread protests during the years 2015 and 2016, associated with the #FeesMustFall and#RhodesMustFall movements. Using a sample of 1905 respondents, over these two years, structural equation models are used to test the contributions of academic adjustment to academic performance for first year accounting students, during the time of these protests. Three theoretical models are tested to explore the persistence of historically discriminatory legacy effects. No differences are found by ethnicity for the influence of academic adjustment difficulties on academic performance. Financially disadvantaged students are however found to be more vulnerable to the influence of financial disadvantage ‒ those receiving financial aid score lower in assessments, and their academic performance seems to be vulnerable to the academic environment dimension of academic adjustment. It is concluded that historical legacy effects ‒ at least insofar as they relate to student academic adjustment ‒ may be limited to financial resource constraints. More concerted efforts on the part of university administrators and policy makers may be needed to improve the university environment and increase financial support for those who remain affected by historical socio-economic disadvantage.